ЙИРИК МАГИСТРАЛ КАНАЛЛАРНИНГ СУВ РЕСУРСЛАРИНИ ТАҚСИМЛАШ МАСАЛАСИНИНГ МАТЕМАТИК МОДЕЛЛАРИНИ ИШЛАБ ЧИҚИШ - Қудайбергенов, А.А. (SCIENCE and SOCIETY, 2023)
On the basis of nonlinear partial differential equations of Saint-Venant has been developed on the example of the Dustlik canal, a mathematical model for controlling the optimal distribution of water to consumers in sections of the main canal. Also, all internal boundary conditions were developed at the points of the channel sections, taking into account all hydraulic and morphomic parameters of the channel sections.